Respuesta :
Answer:
[tex]y = - 3x + 3[/tex]
Step-by-step explanation:
Use the equation
[tex]y = mx + b[/tex]
Insert m = -3 (slope)
[tex]y = - 3x + b[/tex]
Use (-1, 6) to plug in the values of x and y respectively.
[tex]6 = ( - 3)( - 1) + b[/tex]
[tex]6 = 3 + b[/tex]
[tex]b = 3[/tex]
Hence, the equation is
[tex]y = -3x + 3[/tex]
Answer: [tex]y=-3x+3[/tex]
Step-by-step explanation:
We know that the equation of a line passing through a point (p,q) ans has slope 'a' is given by :-
[tex](y-q)=a(x-p)[/tex]
Given : Point : (p,q) =(-1,6)
Slope : a= -3
Then, the equation of a line passing through a point (-1,6) ans has slope -3 will be :-
[tex](y-6)=-3(x-(-1))\\\\\Rightarrow\ y-6=-3(x+1)\\\\\Rightarrow\ y-6=-3x-3\\\\\Rightarrow\ y=-3x-3+6\\\\\Rightarrow\ y=-3x+3[/tex]
Therefore, the first option will be the right option : [tex]y=-3x+3[/tex]